Crime and investigative reporting in the UK - Colbran, Marianne (Policy Press, 2022)
Drawing on interviews with journalists and police officers, this is the first ethnographic study of crime news reporting in the UK for over 25 years. It shows the impediments to crime reporting that exist in the aftermath of the Leveson Report and considers the future of investigative journalism non-profits.